Language skills in extreme preterm infants of school age - Mendoza Carretero, Rosario; Sáenz-Rico de Santiago, Belén (Revista de Investigación en Logopedia, 2023)
In Spain, the number of premature births is 30,000, being one of the main causes of perinatal mortality. In recent years, thanks to medical advances, the survival rate of this population has increased, which has led to the appearance of new morbidities and comorbidities that may interfere in their learning process. This study is qualitative and longitudinal in nature, with a non-probabilistic convenience sample. The aim of the study was to analyse the language skills of four preterm infants with a gestational age at birth of 28 weeks or less, who are currently in the 4th year of Primary Education, in order to detect possible difficulties in the acquisition and use of language. They were administered the Battery of Objective Language and Criterion-Revised (BLOC-SR) at the chronological age of 8 and 10 years. The results suggest that there are difficulties in the acquisition of language components: in the morphological component, for example, in the use of verb forms, derived nouns, etc.; in the syntactic component, in subordinate clauses of cause and condition, etc.; in the semantic component, in locatives, etc.; and in the pragmatic component, in the use of questions. In conclusion, because of their biological vulnerability due to the interruption of brain maturation due to their early birth, extremely premature children need to strengthen their linguistic skills, including semantic awareness, and it is necessary to design intervention proposals for the school environment.
Keywords: Prematurity; Language development; Learning difficulty; Linguistic communicative competence